2017
DOI: 10.1002/cjoc.201600738
|View full text |Cite
|
Sign up to set email alerts
|

Structural Dependence of Competitive Adsorption of Water and Methanol on TiO2 Surfaces

Abstract: Employing TiO 2 anatase (001)-(1×4), rutile (110) and rutile (011)-(2×1) single crystal surfaces, we comprehensively studied the effects of TiO 2 surface structures on the competitive adsorption of water and methanol by means of low energy electron diffraction, thermal desorption spectra and X-ray photoelectron spectroscopy. The relative adsorption strengths of chemisorbed methanol and water vary with the TiO 2 surface structures and the adsorption sites. This leads to TiO 2 surface structure-dependent competi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
3
7
0
Order By: Relevance
“…As indicated by the desorption temperature, the binding strength of HCHO with the Ti 5c sites (310 K) is stronger than the binding strength of H 2 O with Ti 5c sites (270 K), while the binding strength of HCHO with oxygen vacancy sites (435 K) is weaker than the binding strength of hydroxyl groups with oxygen vacancy sites (480 K). The competitive adsorption behavior of HCHO and water on the rutile TiO 2 (011)-(2 × 1) surface is similar to the previously reported competitive adsorption behavior of CH 3 OH and water …”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…As indicated by the desorption temperature, the binding strength of HCHO with the Ti 5c sites (310 K) is stronger than the binding strength of H 2 O with Ti 5c sites (270 K), while the binding strength of HCHO with oxygen vacancy sites (435 K) is weaker than the binding strength of hydroxyl groups with oxygen vacancy sites (480 K). The competitive adsorption behavior of HCHO and water on the rutile TiO 2 (011)-(2 × 1) surface is similar to the previously reported competitive adsorption behavior of CH 3 OH and water …”
Section: Resultssupporting
confidence: 88%
“…Figure 1 shows the TDS spectra of HCHO (m/z = 30, Figure 1A) and C 2 H 4 (m/z = 27, Figure 1B) following various HCHO exposures on the rutile TiO 2 (011)-(2 × 1) surface at 110 K. Likely desorption products were first examined by comprehensively monitoring various QMS m/z signals of 2,15,16,18,26,27,28,29,30,31,32,39,43,44,46,54,56, and 60, and only desorption traces of HCHO and C 2 H 4 were observed. In the TDS spectra of HCHO (Figure 1A), two HCHO desorption features were observed at 435 and 310 K following an exposure of 0.01 L HCHO.…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies of other materials showed that methanol may adsorb and form a methoxy group. Water may subsequently react with the methoxy group to reform gas-phase methanol. Such interactions could explain the transient changes in methanol. However, under identical conditions, no methoxy groups were observed during operando FT–IR of UiO-67-Pt .…”
Section: Resultsmentioning
confidence: 99%
“…Various QMS m / z signals of 2, 15, 16, 18, 26, 27, 28, 29, 30, 31, 32, 44, 46, and 60 were monitored during the TDS experiments, and only the signals of CH 3 OH and CH 4 were observed. Figure A,B, respectively, shows the TDS spectra of CH 3 OH ( m / z = 31) and CH 4 ( m / z = 16) for the TiO 2 (011)-(2 × 1) surface exposed to various amounts of CH 3 OH at 110 K. With increasing CH 3 OH exposure, four desorption features of CH 3 OH were observed at 450, 370, 203, and 150 K, respectively, attributed to the recombinative desorption of CH 3 O br and O br H on TiO 2 and the desorption of CH 3 OH adsorbed on the Ti 5c site, the O 2c site, and the multilayer CH 3 OH, which is consistent with the previous results. , Meanwhile, CH 4 was observed at 688 K from the chemisorbed CH 3 OH on the TiO 2 (011)-(2 × 1) surface, and its desorption peak saturates after 0.02 L CH 3 OH exposure. This agrees with the results on a (011)-facetted TiO 2 (001) surface …”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, as a simple prototype for many organic compounds, methanol is adopted as the probe molecule for the fundamental studies of complex photocatalytic reactions on oxide surfaces. Therefore, photocatalytic surface chemistry of CH 3 OH has been extensively studied on various types of TiO 2 single-crystal surfaces in recent decades. Methanol molecules undergo TiO 2 surface-dependent photocatalytic reactions, and an interesting reaction is the photocatalytic formation of methyl formate (HCOOCH 3 ) first reported on the rutile TiO 2 (110) surface by different groups independently. Later, this reaction was also observed on rutile TiO 2 (011)-(2 × 1) and anatase TiO 2 (101) surfaces. ,, Although it is accepted that methyl formate is formed by the coupling of methoxy (CH 3 O) species and formaldehyde species resulting from the photocatalytic oxidation of methoxy species, the detailed reaction mechanism is not clear. Phillips et al proposed a transient formyl (HCO) species as the intermediate to couple with methoxy to produce HCOOCH 3 on rutile TiO 2 (110) illuminated by UV light, while Guo et al proposed the presence of reaction intermediate of hemiacetal (CH 3 OC­(O)­H 2 ) rather than formyl illuminated by UV laser radiation, which was supported by later density functional theory calculations .…”
Section: Introductionmentioning
confidence: 99%